Konsep Khauf dan Roja' al-Ghazali Dalam Perspektif Rudolf Otto - Mohammad Nizar; Ustadi Hamsah (Philosophiamundi, 2024)
This research seeks to dig and describe information about the concepts of Khauf and Roja’ Al-Ghazaliin depth through Rudolf Otto’s thinking about the daunting and fascinating aspects of religious experience. The concept of Khauf and Roja’ Al-Ghazalican be found in his monomental work, the book of Ihya’ Ulumiddin, whereas the daunting and fascinating used to read al-Ghazali’s thoughts is found in Rudolf Otto’s book The Idea of the Holy. The research focuses on the concept of the religious experience of the two works. In the Bible, it is said that God is God, and that he is the God of all things. In Rudolf Otto's glasses, the two Al-Ghazaliconcepts are built on the basis of the religious experience of Al Ghazali, and both concepts can be categorized as both daunting and fascinating aspects